Synthesis and characterization of NCL-5, NCL-6 and NCL-7: new zeolites enriched with polymorph B of the BEA family - Kadgaonkar, Mahesh D.; Kasture, Mahesh W.; Bhange, Deu S.; Joshi, Praphulla N.; Ramaswamy, Veda; Gupta, Narendra M.; Kumar, Rajiv (Microporous and Mesoporous Materials, 2007)
The synthesis of all-silica analogs of polymorph B-enriched zeolites of the BEA family denoted as NCL-5, NCL-6 and NCL-7 was realized hydrothermally at lower water content in fluoride medium using perchloric acid as promoter and terraethylammonium hydroxide as template. The present article explains the effect of different synthesis parameters on NCL-5, NCL-6 and NCL-7. The samples were characterized using XRD, low temperature N-2-adsorption, Si-29 MAS NMR and FTIR spectroscopy. The phase composition of the structures was derived using simulated patterns for the random intergrowths of polymorphs A and B using DIFFaX Code. The stacking direction c' is perpendicular to the a'b' plane of the layer. The phase composition of polymorph B derived using DIFFaX code was found to be 90-95%. 70-75% and 60-65% in NCL-5, NCL-6 and NCL-7, respectively. The gradual decrease of polymorph B concentration in these samples showed a correlation with the decrease in water/SiO2 molar ratio in gel. The framework FTIR spectral analysis of NCL-5 and all-silica-beta supported the postulation that significant enrichment of polymorph B in NCL-5 compared to that in all-silica-beta, as indicated by the relative intensities of pair of bands at 1097 and 1018 cm(-1) and 460 and 423 cm(-1) vibrations, leads to more tortuous channel structure associated with polymorph B. (C) 2007 Elsevier Inc. All riahts reserved.
Keywords: BEA family; NCL-5; NCL-6; NCL-7; polymorph B enrichment; synthesis; zeolites